Monopoly Practice of PT. Carrefour Indonesia After Acquiring The Shares of PT. Alfa Retailindo: Study of KPPU Decision Number 09/KPPU-L/2009 - Kabul, Kuirinus; Haryanto, Hendra; Kusumadewi, Yessy (Justice Voice, 2023)
The study of The Decision of KPPU Number 09/KPPU-L/2009 to obtain an overview of the reasons for the KPPU to decide that Carrefour has committed monopolistic practices and the legal impact of the decision. By using the juridical research method, that is examining the KPPU’s decision to obtain data on the KPPU’s reasons for stating that PT. Carrefour Indonesia (hereinafter referred to as Carrefour) has committed monopolistic practices and unfair business competition. Where after the acquisition of PT. Alfa Retailindo shares, Carrefour managed to control the market by 57.999% and to achieve this position, Carrefour implemented various market entry barriers. Other business actors cannot enter the relevant market. Such barriers may include the imposition of different entry fees from one company to another. Because Carrefour was found guilty, the KPPU ordered that Carrefour must return Alfa’s shares. The problem is that Law Number 5 Year 1999 does not have provisions governing the mechanism for returning the shares. Thus, KPPU should amend Law Number 5 Year 1999 specifically related to the mechanism for returning shares resulting from acquisitions.